Whole Person Care A New Paradigm for the 21st Century - Hutchinson, Tom A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
A ground-breaking new volume and the first of its kind to concisely outline and explicate the emerging field of whole person care process, Whole Person Care: A New Paradigm for the 21st Century organizes the disparate strains of literature on the topic. It does so by clarifying the concept of 'whole person' and also by outlining the challenges and opportunities that death anxiety poses to the practice of whole person care. Whole person care seeks to study, understand and promote the role of health care in relieving suffering and promoting healing in acute and chronic illness as a complement to the disease focus of biomedicine. The focus is on the whole person -- physical, emotional, social, and spiritual. Using concise, easy-to-read language, the early chapters offer practitioners a thorough understanding of the concepts, skills and tools necessary for the practice of whole person care from a clinician-patient interaction standpoint, while the last two chapters review the myriad implications of whole person care for medical practice. An invaluable resource for all areas of medical practice and for practitioners at all stages of development, from medical students to physicians and allied health providers with many years of experience, Whole Person Care: A New Paradigm for the 21st Century will have a profound impact on western medical practice in North America and elsewhere.
Acknowledgments -- Preface -- Foreword -- Whole person care -- Suffering, whole person care, and the goals of medicine -- The healing journey -- The challenge of medical dichotomies and the congruent physician / patient relationship in medicine -- Separation-attachment theory in illness and the role of the healthcare practitioner -- Empathy, compassion and the goals of medicine -- Mindfulness and whole person care -- Healing, wounding, and the language of medicine -- Death anxiety: the challenge and the promise of whole person care -- Whole person self-care: self-care from the inside out -- Prevention and whole person care -- Whole person care and complementary and alternative therapies -- Spiritual dimensions of whole person care -- Whole person care and the revolution in genetics -- Whole person care on a busy medical ward -- Teaching whole person care in medical school -- Whole person care, professionalism, and the medical mandate -- Whole person care: Conclusions -- Appendix.
Keywords: Geriatrics; Internal medicine; General practice (Medicine).; Anesthesiology; Neurology .; Geriatrics/Gerontology.; Internal Medicine; General Practice / Family Medicine; Anesthesiology; Neurology